Ten-year trajectory of coronary artery calcification and risk of cardiovascular outcomes: the Multi-Ethnic Study of Atherosclerosis - Xie, Changming; Luo, Dongling; Liu, Guodu; Chen, Jie; Huang, Hui (Frontiers in Cardiovascular Medicine, 2024)
Introduction Whether and how coronary artery calcification (CAC) progress contributes to cardiovascular outcomes has not been fully elucidated. This study aims to identify different patterns of CAC change and evaluate the associations with different cardiovascular outcomes.Methods Data from MESA study were analyzed. Participants with at least three CT measurements were included. Main study outcome is hard cardiovascular disease (CVD). CAC scores were determined as phantom adjusted Agatston scores. A group-based trajectory model was used to identify latent groups and estimated the hazard ratios and 95% confidence intervals using Cox proportional regression models.Results 3616 participants were finally enrolled (average age 60.55[9.54] years). Four distinct trajectories were identified: class1, low-stable (24.17%); class2, low-increasing (27.60%); class3, moderate-increasing (30.56%) and class4, elevated-increasing (17.67%). During 13.58 years of follow-up, 291 hard CVD happened. The event rates of hard CVD per 1000 person-years were 2.23 (95%CI 1.53, 3.25), 4.60(95%CI 3.60, 5.89), 7.67(95%CI 6.38, 9.21) and 10.37(95%CI 8.41, 12.80) for class 1 to class 4. The graded positive associations with hard CVD were observed in subgroups of age, gender, race, with presence or absence of hypertension or diabetes.Risk factors for the onset and progression of CAC could possibly differ: age, male gender, history of hypertension and diabetes are consistently associated with the low-, moderate-and elevatedincreasing trajectory. However, Caucasian race, cigarette smoking and a higher BMI was related only to risk of progression but not to incident CAC.